Editorial - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to the spring 2023 issue of the Scottish Journal of Residential Child Care. We have very exciting news for regular readers and authors. The Journal’s editorial team is engaged in a project with colleagues in the Information Services Division at the University of Strathclyde which will lead to improvements in the reach of the Journal, both professionally and internationally. The project involves adding all articles in the Journal’s 20-year back catalogue to the University’s institutional repository, Strathprints.